Enhancing Neuroplasticity via vagus nerve stimulation to improve urinary dysfunction after spinal cord injury: a perspective - Mia J. Sargusingh; Juliet J. A. Addo; Margot S. Damaser; Philippe Zimmern; Seth A. Hays; Ana G. Hernandez-Reynoso (Bioelectronic Medicine)
Abstract One problematic and undertreated consequence of spinal cord injury (SCI) is urinary dysfunction. Treatment is usually conservative, involving regulation of fluid intake and scheduled bladder emptying through intermittent catheterization. These interventions provide symptomatic relief but are associated with recurrent urinary tract infections and increased risk of kidney disease. Neuromodulation has been used to counteract aberrant signals, such as bladder overactivity, but has yet to address other symptoms, such as urethral sphincter tonic activity or poor bladder compliance. Combining rehabilitation with vagus nerve stimulation (VNS), which is known to engage neuromodulatory nuclei to promote synaptic neuroplasticity and recovery, has emerged as a potential therapy to restore function after neurological injury including SCI. Our perspective is that a congruent strategy of pairing VNS with bladder function after incomplete SCI can promote neuroplastic changes in spared neural pathways to strengthen neural control of bladder function.